SenLeash:a restricted defense mechanism against wormhole attacks in wireless sensor network - Rong-hua HU; Xiao-mei DONG; Da-ling WANG (Tongxin xuebao)
The problem of wormhole attacks during neighbor discovery and route discovery phase was studied and a re-stricted mechanism,SenLeash,was presented to restrict the transmission range of messages and hence prevent wormhole attacks in WSN.The SenLeash depends on two factors:the distance of each node to an initial sink node and a chosen re-ceiving distance.To obtain the distance of each node an initial sink node,a RSSI-based measure method nRSSI was proposed.Considering the receiving probability of each node and the maximum retransmission times of the MAC layer,the method of choosing an appropriate receiving distance was discussed.The simulation results demonstrate that the SenLeash can effectively decrease the number of invalidy neighbor nodes and invalidly reply messages caused by worm-hole attacks in WSN.